Designing User Interface On Pinpori Application By Applying Prototype Method - Septiani, Hilda; Fadilah, Evi (International Journal of Education, Information Technology, and Others, 2024)
The general objective of this research is to discuss the application of the prototype method in developing a user interface for the PINPORI program. To improve the quality and benefits of the PINPORI application, several suggestions can be implemented. First, improve user interaction by adding a discussion forum feature to share information and experiences, integrate the “question and answer” feature with a chatbot or online help service, and encourage users to provide feedback. Second, enrich content and features by adding an “inspirational story” feature, providing more detailed information about awards, and developing an “achievement map” feature. Third, increase community engagement by organizing contests or competitions, offering prizes or awards, and collaborating with organizations or communities. By implementing these suggestions, the PINPORI app is expected to become a more interactive, informative and useful platform for the community, and strengthen the positive relationship between the police and the community.